The fall armyworm Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) and some transgenic plants - Zenner de Polanía, Ingeborg; Arévalo, Helber A.; Mejía, Rodolfo (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2011)
Based on preliminary experimental data, and a critical review of studies executed in North and South America, the possibility of the existence of two strains or biotypes of fall armyworm (FAW), Spodoptera frugiperda, in Colombia was studied. Moreover, its influence on the management of this polyphagous pest and the prospects of controlling the insect with transgenic corn and cotton hybrids that express one or more Bacillus thuringiensis toxins were analyzed and discussed. Based on the similarity of CL50 obtained during evaluations for tolerance to Bt toxin Cry1Ac of different FAW strains collected on different hosts and in diverse geographic regions, the existence of a strain that attacks both corn and cotton and another one that affects rice and pastures has been assumed. Populations collected from corn and cotton exhibited a tolerance up to 127 times higher than that of pasture population, which further showed a CL50 to the toxin Cry1Ab between 3.45 and 5.64 ppm. Likewise, some advances in the attainment of plant species, genetically transformed hosts of the insect with toxins different from those coming from Bt, have been shown and evaluated at an international level.